A CASE OF METABOLIC SYNDROME - Khoo Ee Ming; Rabia Khatoon (Malaysian Family Physician, 2006)
This case report illustrates a 40-year-old woman who presented with chest discomfort that was subsequently diagnosed to have metabolic syndrome. Metabolic syndrome is a common condition associated with increased cardiovascular morbidity and mortality. As primary care providers, we should be detect this condition early, intervene and prevent appropriately before complications occur.